Between State and Family: Discussion on the Segregation and Integration of the Daily Living Space within Shanghai Historic Lane Neighborhood. (2nd September 2019) - Zhou, Xiang; Cheng, Yuning
Abstract: Based on the phenomenon of social segregation that commonly appears in contemporary cities, the article points out the peculiar problem of adjacent segregation that currently occurs in the historic lane neighborhood of Shanghai. By discussing the dialectical relation between adjacent segregation and mixed habitation, it indicates physical proximity does not necessarily result in social mix. After that, by taking the lane neighborhood in Hongkou creek area as the research object, the article streamlines its historical transition. Meanwhile, through the measurements of community cognitive domain and daily spatial utilization pattern, the article explores residents' perception of 'three discrepant worlds' of Hongkou creek area. Then, by confirming the social value of daily living space, the article summarizes the organization mechanism on account of community cohesion from the perspective of the state and the family. Finally, it concludes that the maintenance of daily living space on the material level and the support of community empowerment on the social level are a viable solution for the historic lane neighborhood to redress the adjacent segregation and unify public space against the context of rapid urbanization.